32 of 1640 Letters from Theresa Paolone (Toronto : NIAV Publications, 1980)
Thirty-two provocative form letters remaining in Paolone's possession from a total of 1640 composed in order to make up for a lifetime of neglected correspondance are compiled in Greyson's artist's book.
Engels
boek
Keywords: Greyson, John